Mapping the impact of exposure to maternal immune activation on juvenile Wistar rat brain macro- and microstructure during early post-natal development. (November 2019) - Wood, Tobias C.; Edye, Michelle E.; Harte, Michael K.; Neill, Joanna C.; Prinssen, Eric P.; Vernon, Anthony C.
Maternal immune activation is consistently associated with elevated risk for multiple psychiatric disorders in the affected offspring. Related to this, an important goal of our work is to explore the impact of maternal immune activation effects across the lifespan. In this context, we recently reported the effects of polyriboinosinic-polyribocytidylic acid–induced maternal immune activation at gestational day 15, immediately prior to birth, at gestational day 21 and again at post-natal day 21, providing a systematic assessment of plasma interleukin 6, body temperature and weight alterations in pregnant rats and preliminary evidence for gross morphological changes and microglial neuropathology in both male and female offsprings at these time points. Here, we sought to complement and extend these data by characterising in more detail the mesoscale impact of gestational polyriboinosinic-polyribocytidylic acid exposure at gestational day 15 on the neuroanatomy of the juvenile (post-natal day 21) rat brain using high-resolution, ex vivo anatomical magnetic resonance imaging in combination with atlas-based segmentation. Our preliminary data suggest subtle neuroanatomical effects of gestational polyriboinosinic-polyribocytidylic acid exposure (n = 10) relative to saline controls (n = 10) at this time-point. Specifically, we found an increase in the relative volume of the diagonal domain in polyriboinosinic-polyribocytidylic acid offspring (p < 0.01 uncorrected), which just failed to pass stringent multiple comparisons correction (actual q = 0.07). No statistically significant microstructural alterations were detectable using diffusion tensor imaging. Further studies are required to map the proximal effects of maternal immune activation on the developing rodent brain from foetal to early post-natal life and confirm our findings herein.